Alpha Blocker and 5-Alpha Reductase Inhibitor Prescribing Habits among Urologists and Primary Care Physicians. Issue 4 (July 2019) - Chua, Kevin J.; Li, Gen; Rutman, Matthew P.; Hyams, Elias S.
Abstract: Introduction: While primary care physicians often prescribe medical therapy for voiding symptoms attributed to benign prostate enlargement, it is not clear to what extent they use novel or varied agents. We describe alpha blocker and 5-alpha reductase inhibitor prescribing habits of primary care physicians and compare them with those of urologists. Methods: Within Medicare Part D we identified providers who prescribed alpha blockers and 5-alpha reductase inhibitors in 2015. We determined the proportions that prescribed 1 versus multiple agents, different types of agents and both types of medications, and compared them between providers. Results: Overall 94% (9, 327) of urologists, 50% (54, 253) of internal medicine physicians and 61% (60, 063) of family medicine physicians prescribed an alpha blocker in 2015. Urologists were more likely to prescribe multiple alpha blockers. However, they were also more likely to predominantly use a single agent. A higher percentage of urologists prescribed newer agents (alfuzosin, silodosin) while a higher percentage of primary care physicians prescribed older agents (terazosin, doxazosin). For 5-alpha reductase inhibitors 87.5% (8, 692) of urologists, 32.0% (34, 598) of internal medicine physicians and 34.4% (33, 720) of family medicine physicians issued prescriptions. Urologists were more likely to prescribe a single 5-alpha reductase inhibitor predominantly and prescribe multiple 5-alpha reductase inhibitors. More primary care physicians prescribed alpha blockers without also prescribing 5-alpha reductase inhibitors. Conclusions: Most primary care physicians prescribed alpha blockers to Medicare beneficiaries. Urologists were more likely to use diverse as well as newer agents, signaling greater awareness of medical options, although also more complex cases. Urologists were more likely to habitually prescribe single medications. As primary care physicians are involved in the initial treatment of these patients, further education regarding medical options and appropriate indications should be considered.